REDEFINING MULTICULTURAL EDUCATION (Author: Ratna Ghosh) - Ray, Douglas (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1996)
RATNA GHOSH. Redefining Multicultural Education. Toronto: Harcourt Brace. 1996. $16.95. 126 pp. ISBN 7747-32768.